Using virtual satellites for navigation definitions - Ковалевський, Е.О. (Proceedings of National Aviation University, 2008)
Methods of navigational determinations with using of a priori information about non visible satellites are offered. Effectiveness of this method investigated with the help of mathematical modeling.